Uncovering urban food-energy-water nexus based on physical input-output analysis: The case of the Detroit Metropolitan Area. (15th October 2019) - Feng, Cuiyang; Qu, Shen; Jin, Yi; Tang, Xu; Liang, Sai; Chiu, Anthony S.F.; Xu, Ming
Graphical abstract: Highlights: Establishing an urban food-energy-water physical input-output (FEW-PIO) model. Identifying key sectors by comparing consumption-based and production-based results. Adopting structural path analysis to identify critical supply chain paths of food-energy-water flows. Identifying co-benefit opportunities of food-energy-water nexus to promote synergies and reduce tradeoff. Decision support for sustainable urban food-energy-water development. Abstract: Secure and efficient supply for the food, energy and water resources is essential for sustainable urban development. Due to the close interaction of food, energy and water systems, it is necessary to analyze food-energy-water nexus from an integrated perspective. Taking the Detroit Metropolitan Area as a case, this study first constructs a food-energy-water physical input-output model to quantify food, energy and water flows. Then, structural path analysis is adopted to identify critical supply chain paths driven by the final demand of key sectors. Quantitative results of food-energy-water flows show that major inputs of food and energy in the Detroit Metropolitan Area are from outside through imports, while water use is predominately extracted from local sources. Local consumption activities for the food, energy, and water systems are mainly concentrated downstream of the supply chain. Structural path analysis results show that intermediate processes use relatively large amounts of food, energy and water, and should be more concerned. Also, identifying sectors involving multiple systems, such as Food Processing, Domestic Consumption, Solid Waste Management, Wastewater Treatment, and Residual Processing, can promote co-benefit opportunities. This holistic view on urban FEW nexus presented in this study can facilitate better decisions and help avoid unintended consequences.